Resepsi Fungsional Al-Qur - Baihaqi, Nurun Nisaa; Munshihah, Aty (NALAR, 2022)
The ritual of reading the verses of the Qur'an in a tradition in society is an interesting phenomenon to study. The reason is that in the study of the Living Qur'an, the Qur'an as the main source of teachings is not only understood as hermeneutical. This research focuses on the functional reception of the Dusun Tundan community towards the ritual of reading certain verses of the Qur'an in the Nyadran Tradition. The type of research is qualitative-descriptive, namely research that aims to understand what phenomena are experienced by research subjects. In this case, the author uses functional reception theory to understand the various reactions and responses of the community to the ritual. The results of the study indicate that there is a functional reception in the ritual of reading certain verses of the Qur'an which is described as follows; First, the reading of the verses is intended to calm the soul and forgive all its sins. Second, pragmatically, reading verses for participants is considered good, correct, and useful because it makes people's hearts calm and can feel the presence of spirits. Third, reading the verses awakens a person to respect and appreciate other people, especially parents who are still alive. Fourth, the sowing of flowers in another ritual The Nyadran tradition is analogous to the planting of two wet date palms by the Prophet Muhammad as a symbol of the forgiveness of the soul. Practically, the Nyadran Tradition is also a place to build social interaction.Keywords :